Nutritional Composition of Macroalgae in Tanjung Tuan, Port Dickson, Malaysia - Salleh, Aishah; Ahmad Wakid, Sarini (Malaysian Journal of Science, 2008)
There are diverse species of macro algae in Tanjung Tuan, Port Dickson that include the division of Phaeophyta such as Padina gymnospora (KÃ¼tzing) Vikcers, Sargassum baccularia C. Agardh, Sargassum binderi Sonder, and Turbinaria conoides (J. Agardh) KÃ¼tzing together with the division of Chlorophyta such as Caulerpa lentillifera J.Agardh and Caulerpa racemosa (Forsskal) J. Agardh. Nutritional compositions of samples collected were determined. Content analysis of moisture, ash, protein, carbohydrate, crude fiber, fat content, vitamins (vitamin A, vitamin Bâ‚, vitamin Bâ‚‚, vitamin C, Niacin) and minerals (phosphorus, sodium, potassium, calcium, iron, magnesium, copper and zinc) of the selected macroalgae had been carried out using standard methods. Comparisons with corresponding nutrient values in several commonly consumed local vegetables (spinach), local macro algae e.g. Gracillaria changii and macro algae or macroalgae derived-products from other countries e.g. Dulse, Irish Moss, Kombu, Nori, Wakame, seaweed agar (raw) were done. Turbinaria conoides showed the overall. best reading compared to five other species because it showed higher contents of ash (4.7 %), vitamin A (24.1 mg/kg, 80333 IU), niacin (274 mg/kg), sodium (13085 mg/kg), potassium (21137 mg/kg), calcium (2353 mg/kg), magnesium (4026 mg/kg), copper (25.2 mg/kg) and zinc (49.1 mg/kg).